Towards understanding the behavior of polyelectrolyte–surfactant mixtures at the water/vapor interface closer to technologically-relevant conditions. Issue 3 (3rd January 2018) - Llamas, Sara; Fernández-Peña, Laura; Akanno, Andrew; Guzmán, Eduardo; Ortega, Víctor; Ortega, Francisco; Csaky, Aurelio G.; Campbell, Richard A.; Rubio, Ramón G.
Abstract : The adsorption of technologically relevant polyelectrolyte–surfactant mixtures at fluid interfaces was studied by neutron reflectometry and surface tensiometry. Abstract : Polyelectrolyte–surfactant mixtures and their interactions with fluid interfaces are an important research field due to their use in technological applications. Most of the existing knowledge on these systems is based on models in which the polyelectrolyte concentration is around 50 times lower than that used in commercial formulations. The present work marks a step to close the gap on the understanding of their behavior under more practically-relevant conditions. The adsorption of concentrated mixtures of poly(diallyldimethyl-ammonium) chloride and sodium N -lauroyl- N -methyltaurate at the water/vapor interface with a crude mixing protocol has been studied by different surface tension techniques, Brewster angle microscopy, neutron reflectometry, and several bulk characterization techniques. Kinetically-trapped aggregates formed during mixing influence the interfacial morphology of mixtures produced in the equilibrium one-phase region, yet fluctuations in the surface tension isotherm result depending on the tensiometric technique applied. At low bulk surfactant concentrations, the free surfactant concentration is very low, and the interfacial composition matches the trend of the bulk complexes, which is a behavior that has not been observed in studies on more dilute mixtures. Nevertheless, a transition to synergistic co-adsorption of complexes and free surfactant is observed at the higher bulk surfactant concentrations studied. This transition appears to be a special feature of these more concentrated mixtures, which deserves attention in future studies of systems with additional components.